2010
DOI: 10.1007/s12149-009-0338-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations between liver 18F fluoro-2-deoxy-d-glucose accumulation and various clinical parameters in a Japanese population: influence of the metabolic syndrome

Abstract: BMI was the strongest determinant of liver (18)F-FDG uptake, and the liver (18)F-FDG uptake of metabolic syndrome subjects was significantly higher than that of non-metabolic syndrome subjects. This result suggests that a subject with a high liver (18)F-FDG uptake should be screened for the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 15 publications
10
34
1
Order By: Relevance
“…A similar result was reported by Kamimura et al [17]. A similar result was reported by Kamimura et al [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A similar result was reported by Kamimura et al [17]. A similar result was reported by Kamimura et al [17].…”
Section: Discussionsupporting
confidence: 90%
“…A positive impact of BMI on the background liver uptake of 18 F-FDG was reported previously, with β-coefficients reported as ranging from 0.035 to 0.059 [11,14,17]. Our study confirmed that high BMI patients had greater liver 18 F-FDG uptake compared with low BMI patients, although the ApoA, apolipoprotein-A (g/l); ApoB, apolipoprotein-B (g/l); ApoE, apolipoprotein-E (mg/l); BGlu, blood glucose (mg/dl); Lp(a), lipoprotein-a (mg/l); NHDL, non-HDL cholesterol (mmol/l); SUV, standardized uptake value; TC, total cholesterol (mmol/l); TG, triglyceride (mmol/l).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Other authors also found that in patients with no known diabetes, liver 18 FDG uptake increases with blood glucose level. 13,14 A possible explanation for this phenomenon is that the liver is a key organ responsible for glucose metabolism through gluconeogenesis and glycogen storage. 13 On the other hand, blood glucose level has an opposite effect on tumor uptake, so that many investigators would correct for this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous reports described the SUV max associated with fat accumulation as high as approximately 3.5 inches. 18,19 However, as the increased FDG uptake associated with H-HCA led to higher SUV max , we suspect that the above-mentioned alternative factors had no significant effect on the increased FDG uptake in the present cases.…”
Section: Discussionmentioning
confidence: 64%